Innovation in leadership and team performance: evidence from Indonesia property agent industry - Purwadita, Christianto Prasetyo; Sudiro, Achmad; Mugiono, Mugiono; Idris, Idris (MEC-J (Management and Economics Journal), 2018)
This research aims to examine the role of innovation in the effects of transactional and transformational leadership on team performance at PropNext Reality Indonesia. The sample consist of 90 team members of PropNext Reality Indonesia. To examine the hypotheses and mediation variable, this research used Partial Least Square (PLS) and sobel test online. This research found that all hypotheses tested were positive and significant except the first hypothesis, transactional leadership has no significant effects on team performance. In addition, it also found that innovation can mediate the relationship between transactional or transformational leadership on team performance. These results confirmed and contradicted to the previous studies conducted.